2015
DOI: 10.1111/ejn.12879
|View full text |Cite
|
Sign up to set email alerts
|

The role of stop‐signal probability and expectation in proactive inhibition

Abstract: The subjective belief of what will happen plays an important role across many cognitive domains, including response inhibition. However, tasks that study inhibition do not distinguish between the processing of objective contextual cues indicating stop-signal probability and the subjective expectation that a stop-signal will or will not occur. Here we investigated the effects of stop-signal probability and the expectation of a stop-signal on proactive inhibition. Twenty participants performed a modified stop-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 64 publications
18
70
0
Order By: Relevance
“…This slowing is in line with previous work (Verbruggen and Logan, 2008; Jahfari et al, 2012; Zandbelt et al, 2013; Vink et al, 2015). Moreover, participants committed more premature errors during the CG than during in the MS condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This slowing is in line with previous work (Verbruggen and Logan, 2008; Jahfari et al, 2012; Zandbelt et al, 2013; Vink et al, 2015). Moreover, participants committed more premature errors during the CG than during in the MS condition.…”
Section: Discussionsupporting
confidence: 93%
“…However prefrontal activity was not elicited in a sustained manner before target onset, but only transiently after target signals. This is against the predictions of the DMC, but dovetails recent findings in other motor inhibition paradigms (Swann et al, 2012, 2013; Zandbelt et al, 2013; Vink et al, 2015). In the following, we will first discuss behavioral results and then refer to results pertaining to the different aspects of proactive and reactive control implied in the DMC model, namely visual attention, prefrontal control and sensorimotor activity.…”
Section: Discussionsupporting
confidence: 87%
“…This indicates that response modulation results from the interplay between FFA_R and these high-level areas. This type of interplay is supported by previous studies that demonstrated the inferior frontal and parietal cortices to be involved in probability-related processing222324. Therefore, through the identification of the involvement of the high-level areas IFG_L and IPL_L, the present study indicates that response enhancement and repetition suppression are attributable to top-down modulation more directly than previous studies did and suggests a brain network related to perceptual expectation1125.…”
Section: Discussionsupporting
confidence: 88%
“…This replicates previous findings of increasing RT with higher proportions of stop trials in the SST or no-go trials in the Go-NoGo paradigm (Wijeakumar et al, 2015; Zandbelt and Vink, 2010). However, SSRT did not significantly differ between the two experimental conditions, suggesting that whether or not stopping was the more frequent response did not alter the efficiency of response inhibition, again replicating previous work (Vink et al, 2015; Zandbelt et al, 2013). …”
Section: Discussionsupporting
confidence: 85%